Implantation of C2 prosthesis with dorsal fusion C0-C4 due to pathologic C2 fracture. Case report and literature review - Feuerstein, Laurin; Martens, Benjamin; Schwizer, Roman; Forster, Thomas; Ziga, Michal (Archives of orthopaedic and trauma surgery, 2024)
INTRODUCTION: Pathological destruction of the axis vertebra leads to a highly unstable condition in an upper cervical spine. As surgical resection and anatomical reconstruction of the second cervical vertebrae represents a life threatening procedure, less radical approaches are preferred and only few cases of C2 prosthesis are described in literature. CASE DESCRIPTION: The focus of this case report is a 21-year-old man with a pathological fracture of C2 managed primarily surgically with the C1-C3 dorsal fusion. Due to the progression of giant cell tumor and destruction of the axis vertebra, C2 prosthesis through anterior approach and dorsal occipito-cervical fusion C0-C4 were performed. Postoperative infection was managed surgically with a 2-staged dorsal debridement, ostheosynthesis material change and autologous bone graft. After a 4 week-intravenous therapy with the ceftriaxone in combination with the amoxicillin/clavulanate, followed by 12 week per oral therapy with amoxicillin/clavulanate in combination with ciprofloxacin, the complete recovery of the infection was achieved. Radiotherapy was initiated 2 months after the last revision surgery and the patient showed a good clinical outcome with stable construct at a 1 year follow-up. A review of literature of all reported C2 prosthesis cases was performed CONCLUSION: C2 prosthesis allows a more radical resection in pathological processes involving the axis vertebra. Combined with the posterior fusion, immediate stability is achieved. Anterior surgical approach is through a highly unsterile oral environment which presents a high-risk of postoperative infection.
Keywords: Humans; Prosthesis Implantation; Spinal Fusion; axis; Spinal Fractures; mladý dospělý; implantace protézy; lidé; fraktury páteře; Spinal Neoplasms; Fractures, Spontaneous; nádory páteře; Male; Axis, Cervical Vertebra; fraktury spontánní; Young Adult; fúze páteře; Cervical Vertebrae; mužské pohlaví; krční obratle